If I do not ask for help, it does not mean I do not need it: Experimental analysis of recipients' procedural preferences for redistribution - Serhiy Kandul; Olexandr Nikolaychuk (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
Experimental literature on pro-social behavior has been largely focused on settings where the decision of donors is sufficient for an interaction to occur. However, in many real-life applications recipients first have to ask donors for help to initiate the transaction. We suggest that this first move by the recipients might be associated with psychological costs which include shame of not being able to manage on one's own, negative feelings from the loss of respect, or stigmatization from the society. We argue that the reluctance to initiate the transaction is different from the unwillingness to accept help initiated by somebody else and test this preposition in a laboratory experiment. We let participants play a dictator game with two procedures: (1) dictator first chooses a transfer, and the recipient decides to accept or reject it; (2) recipient first decides to ask or not, and if asked the dictator then chooses a transfer. We also let recipients choose in which of the two conditions they want to play and then compare recipients' and dictators' behavior within each experimental procedure.
Keywords: D01; D64; D90; 330; dictator game; procedural preferences; fairness; role allocation; social preferences